Does pre-enrichment of anodes with acetate to select for Geobacter spp. enhance performance of microbial fuel cells when switched to more complex substrates? - Christgen, Beate; Spurr, Martin; Milner, Edward M.; Izadi, Paniz; McCann, Clare; Yu, Eileen; Curtis, Tom; Scott, Keith; Head, Ian M. (Frontiers in Microbiology, 2023)
Many factors affect the performance of microbial fuel cells (MFCs). Considerable attention has been given to the impact of cell configuration and materials on MFC performance. Much less work has been done on the impact of the anode microbiota, particularly when using complex substrates as fuel. One strategy to improve MFC performance on complex substrates such as wastewater, is to pre-enrich the anode with known, efficient electrogens, such as Geobacter spp. The implication is that the electrogens are the limiting factor in MFCs fed complex substrates and the organisms feeding the electrogens through hydrolysis and fermentation are not limiting. We conducted a systematic test of this strategy and the assumptions associated with it. Microbial fuel cells were enriched using three different substrates (acetate, synthetic wastewater (OECD) and real domestic wastewater) and three different inocula (Activated Sludge, Tyne River sediment, effluent from an MFC). Reactors were either enriched on complex substrates from the start or were initially fed acetate to enrich for Geobacter spp. before switching to synthetic or real wastewater. Pre-enrichment on acetate increased the relative abundance of Geobacter spp. in MFCs that were switched to complex substrates compared to MFCs that had been fed the complex substrates from the beginning (wastewater-fed MFCs -21.9 ± 1.7% Geobacter spp.; acetate-enriched MFCs, fed wastewater -34.9 ± 6.7% Geobacter spp.; OECD fed MFCs 42.5 ± 3.7% Geobacter spp.; acetate-enriched OECD-fed MFCs -47.3 ± 3.9% Geobacter spp.). However, acetate pre-enrichment did not translate into significant improvements in cell voltage, maximum current density, maximum power density or substrate removal efficiency. Coulombic efficiency (CE) was higher in MFCs pre-enriched on acetate when complex substrates were fed (wastewater-fed MFCs 22.0 ± 6.2 % CE; acetate-enriched MFCs, fed wastewater 58.5 ± 3.5 % CE; OECD fed MFCs 22.0 ± 3.2 % CE; acetate-enriched OECD-fed MFCs 28.7 ± 4.2% CE.) The relative abundance of Geobacter ssp. and CE represents the average of the nine replicate reactors. Efforts to improve the performance of anodic microbial communities in MFCs utilizing complex organic substrates should therefore focus on enhancing the activity of organisms driving hydrolysis and fermentation rather the terminal-oxidizing electrogens.